2017
DOI: 10.1007/s40266-017-0487-1
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of Preventive Medicines in Older People with Limited Life Expectancy: A Systematic Review

Abstract: The review found that withdrawal of preventive medicines at the end of life is challenging. Decisions about the discontinuation of preventive medicines for individuals approaching the end of life are increasingly complicated by the lack of clear deprescribing guidelines for these medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…To our knowledge, no previous study has been carried out to study gender differences in statin discontinuation in patients with advanced cancer disease. In studies on statin discontinuation in non-cancer patients, the majority of the participants have been men [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no previous study has been carried out to study gender differences in statin discontinuation in patients with advanced cancer disease. In studies on statin discontinuation in non-cancer patients, the majority of the participants have been men [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The older population with life‐limiting illness (LLI) and/or limited life expectancy (LLE) frequently face the burden of potentially inappropriate medication (PIM) and polypharmacy, which are known to be associated with poor health outcomes such as reduced quality of life (QOL), adverse drug reactions, falls, hospitalisation and mortality . It has been suggested that diagnosis of LLI or LLE should favour discontinuation of preventive medicines . However, evidence in the literature indicates that older patients continue to receive preventive medicines, or medicines that are not prescribed as symptomatic treatment, without consideration of the diagnosis of LLI .…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews on deprescribing of PIMs or discontinuation of preventive medication in patients with LLI and reduced life expectancy have been conducted . The findings from these reviews illustrate that older patients with LLI and LLE continue to receive preventive medication.…”
Section: Introductionmentioning
confidence: 99%
“…These utilization trends aid in recognizing rational medicine use, access to medicines, and compare observed patterns with evidence and guideline‐based prescribing. Several studies have explored concomitant medicine use in the last year of life, particularly in individuals with limited life expectancy; however, there is limited literature on the patterns of PM use during this time . The present explorative study aimed to examine the prescribing patterns of PM in older individuals in their last year of life.…”
Section: Introductionmentioning
confidence: 99%